Practical analysis of the metabolic response to a resistance training session in male and female sprinters - Wlodarczyk, M.; Kantanista, A.; Kusy, K.; Zielinski, J.; Pospieszna, B. (Trends in Sport Sciences, 2020)
In modern sport, training individualization and detailed analysis of specific patterns of biochemical indices under certain exercises and training sessions is become more and more crucial. Aim of Study. This study aimed to concurrently evaluate the lactate and blood ammonia response during resistance training in four elite sprinters (two men and two women). Material and Methods. Blood samples were taken from the fingertip before and after the warm-up, after each exercise (power cleans, squat jumps, quarter squats and lunges), and at the 10th and 20th min of the cool-down. Results. In male athletes, maximum lactate concentrations were achieved after the power clean exercise, while peak blood ammonia concentrations after squat jumps. In female athletes, peak blood ammonia and lactate concentrations were noted more individually. The course of changes in lactate concentrations was very diverse in each athlete. The ammonia concentration in response to the performed exercises was much more consistent, however still different between individual athletes. Conclusions. A practical analysis of the metabolic response to different exercises in a resistance training session, using lactate and ammonia concentrations, offers vital information that can help coaches better understand internal training load experienced by the athlete and to better adjust the prescribed loads and rest periods to the training targets in future training sessions.